Force majeure and the law - Musgrave, Thomas D., author. Link
1 online resource
Keywords: "This book examines how the Roman, French and English legal systems have each dealt with the issue of unforeseen, supervening events which have rendered the performance of contractual obligations either impossible or fundamentally different in nature, sometimes known as Force Majeure or Acts of God. Although the Roman, French and English laws of contract have each developed legal rules which address this issue, the approach adopted by each system is significantly different from that of the others. The thesis of this book is that the response of a legal system to unforeseen, supervening events derives primarily from the nature and structure of that legal system as a whole, and then, within that broader context, from the salient characteristics of that system's particular law of contract. The work compares the differing nature and structure of the Roman, French and English legal systems, and their respective laws of contract, in order to demonstrate how this is so. The volume will be a valuable guide for academics and researchers working in the areas of Comparative Law, Legal History, Legal Theory and Contract Law. As the English approach to unforeseen, supervening events is very different from that of France, the book will be of benefit both to English and to French practitioners as they seek to understand how supervening events are dealt with across the Channel. It will also appeal to law students as a guide for studying comparative law"--